The Role of Leadership and Talent Development in Enhancing Employee Performance - Irwanta, Tommy; Aribowo, Agus (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study is motivated by the importance of talent development and leadership in enhancing employee performance in e-commerce companies in Indonesia. Employee performance is a key factor in achieving organizational goals, and talent development as well as leadership are considered crucial in this regard. The purpose of this study is to analyze the impact of talent development and leadership on employee performance and to examine whether leadership moderates the relationship between talent development and performance. The study employs multiple linear regression methods to analyze data collected from 131 respondents. The results indicate that both talent development and leadership significantly influence employee performance. Hypothesis testing reveals that talent development and leadership have a significant positive relationship with employee performance, with leadership having a more dominant influence. However, moderation analysis shows that leadership does not significantly moderate the relationship between talent development and employee performance. The conclusion of this study is that talent development and leadership are important factors in improving employee performance, but leadership does not significantly moderate the relationship between talent development and performance. Therefore, e-commerce companies in Indonesia are advised to focus more on talent development and leadership to achieve optimal employee performance.